Tell Me Your Employees' Well-Being and I Will Tell You What You Do as a Leader: Learning from Leaders Through a Qualitative Study - Santos,M.B.; Silva, S.A. (Work, Stress and Health Conference 2023, 2023)
Studies have shown that leadership behaviours can influence employees' levels of well-being. However, employees' well-being can also influence leaders' behaviours. Some of these behaviours were identified in previous studies (for example, monitoring employees and empowering them). Moreover, most studies focus on the employees' perspective, so there is a need to explore from a leaders' perspective the role of employees' well-being in their leadership behaviours. This qualitative study aims to explore, through the leaders' experience, the leadership behaviours most susceptible to the influence of employee well-being, and the resources that can help leaders manage this influence. To develop this research, 25 semi-structured and individual interviews were conducted with leaders. The content was then analysed using a Template Analysis approach. The results revealed that the influence of employees' well-being on leadership behaviours can occur especially when their levels of well-being are low. Additionally, a set of 12 leadership behaviours was analysed which, according to the leaders' perspective, may change due to employees' well-being. In that set of behaviours, assigning tasks and providing support to employees were the most mentioned. The results also helped to identify 20 resources which can help leaders to manage the aforementioned influence. The main resources were the support of colleagues and the team climate. Through the results obtained, it was also recognised the need to make leaders aware of this influence and to develop future research.